Monitoring of Habitats in a Coastal Dune System Within the “Arco Ionico” Site (Taranto, Apulia) - Francesco Maria Todaro; Maria Adamo; Gianmarco Tavilla; Catarina Meireles; Valeria Tomaselli (Land)
Although dune systems play a crucial ecological role and offer various ecosystem services, they are listed among the habitat types of community interest in the European Union that are undergoing the most severe conservation challenges. The subject of this study was the monitoring of habitat types protected under Directive 92/43/EEC (Habitats Directive) along the coastal dune systems of the Taranto Ionian Arc. Vegetation sociological surveys, GIS mapping, landscape metrics, NBR and dNBR indices were employed to assess the conservation status of the dune system and the impact of disturbance factors. Special attention was given to habitat 2250* (Coastal dunes with Juniperus spp.), revealing that it expanded from 2006 to 2019 but then significantly reduced between 2019 and 2022, with increasing fragmentation, mainly due to wildfires. The study also highlighted the impact of invasive species such as Acacia saligna and Carpobrotus acinaciformis, which compete for space and vital resources. These findings provide scientific evidence for the management and restoration of coastal dune ecosystems, emphasizing the need for targeted conservation strategies to mitigate the effects of these disturbances.